Proto-STARS Pilot: A Nine Campus Collaboration to Adapt the STARS Sustainability Assessment to Northeast Boarding Schools. - Hession, Rebecca. (2017)
Abstract: This study evaluates the early implementation of a pilot program of the Sustainability Tracking Assessment and Rating System (STARS), referred to as proto-STARS, which occurred between spring 2010 and spring 2011 at nine northeast boarding schools. The schools comprise the total sample size for the pilot program, and the research focused on an internal comparison. The evaluation centered on clarification of program implementation in three areas: program use, implementation variation and lessons learned. Early implementation was assessed in a qualitative study based on assessment data and interviewee responses. Fewer than half of the schools completed the assessment tool within the projected timeline. Of the schools that reported a sustainability rating, two were Bronze level and two were Silver level. A cross group comparison between the assessment completers and non-completers suggests that few distinguishing factors exist between the two groups. Individual campus circumstances and difficulty collecting necessary data within the pilot program's timeframe might help explain the limited completion rate.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Francine Jacobs.; Keywords: Sustainability, and Secondary education.